Passive leg raising in out-of-hospital cardiac arrest. (April 2019) - Holmén, Johan; Herlitz, Johan; Jimenez-Herrera, Maria; Karlsson, Thomas; Axelsson, Christer
Abstract: Background: The use of passive leg raising (PLR) in cardiopulmonary resuscitation (CPR) is sometimes discussed and even recommended. The effect of this intervention has never been properly addressed. We planned to determine whether PLR in out-of-hospital cardiac arrest (OHCA) is associated with an improved survival to 30 days. Methods: In eight districts in western Sweden, we introduced PLR within five minutes after the start of CPR, among patients with OHCA. Patients in whom PLR was not performed, within the same district, served as a control group. Thirty-day survival was the primary endpoint. A propensity score analysis, as well as a standard multivariate analysis, was used to assess possible differences between the two groups. Results: We identified 3554 patients with OHCA from the eight districts. Forty-four percent were treated with PLR during CPR. Patients who received PLR differed from those who did not, by having more risk factors for an adverse outcome (fewer crew-witnessed cases, more OHCA at home, a greater need for medication and prolonged delays to treatment). The overall survival to 30 days was 7.9% among patients who received PLR versus 13.5% among those who did not. A comparison of the groups, using propensity score matching, revealed a 30 -day survival of 8.6% in the PLR group versus 8.2% in the control group (odds ratio 1.07; 95% confidence interval 0.80–1.44). Conclusion: In an observational study, we introduced PLR as an addition to standard treatment in patients with OHCA. We did not find any evidence that this treatment improves survival to 30 days.